As guest of Allah : with members of Brunei Royal family : a memoir - Awang Abdul Aziz Awang Juned, Pehin Dato Seri Maharaja Dato Paduka Seri Setia Haji (Bandar Seri Begawan, Brunei : Brunei History Centre, Ministry of Culture, Youth and Sports, 1999)
Travel account on the pilgramage of the Brunei Royal family.
'Translated from the Malay edition (Menjadi Tetamu Allah Bersama Ahli Kerabat Diraja : Suatu Sejarah, 1992) by Awang Haji Mohama Amin bin Hassan.'
Keywords: Hassanal Bolkiah Mu'izzaddin Waddaulah, -- Sultan dan Yang Di-Pertuan Negara Brunei, -- 1946-; Sultanate -- Brunei -- History; Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca; Sultans -- Travel -- Saudi Arabia -- Mecca; Brunei -- Sultans; Brunei -- Kings and Rulers -- Journeys -- Saudi Arabia; Brunei -- Kings and rulers -- Family -- Travel -- Saudi Arabia -- Mecca